Electrodeposition of PbO2 on Ti Substrate in Alkaline Solution: Influence of Fluoride Ions Addition - Mukimin, A.; Wijaya, K.; Kuncaka, A. (Asian Journal of Chemistry, 2013)
Titanium-lead dioxide electrode (Ti/PbO2) has been synthesized by the method of anodic electrodeposition from alkaline solutions with a concentration variation of NaF (0.0048-0.0238 M). The results indicated that the presence of F– ions affects the rate of formation of PbO2 which may impact on its properties. SEM analysis showed that the PbO2 film has nanorod-shaped surface morphology with a diameter of 50 nm and a length of 500 nm. X-Ray diffraction study showed that the material was composed of a mixture of a-phase (021; 200; 311) and b-phase (002; 211; 220; 112) whose intensity decreases with an increase on the addition of NaF. Cyclic voltametry results showed a correlation of the electrocatalytic activities with the intensity of phase. The electrocatalytic performance of PbO2 is more likely to be affected by the b-phase (221 and 220) than by the a-phase (021). In other words, the electrocatalytic activity of PbO2 is influenced more by the surface area of the conductivity properties.